Dysregulated metal ion homeostasis underscores non-canonical function of CD8+ T cell during COVID-19 - Khare, Kriti; Chattopadhyay, Partha; Devi, Priti; Mehta, Priyanka; Raina, Aakarshan; Liu, Chinky Shiu Chen; Tardalkar, Kishore; Joshi, Meghnad G.; Pandey, Rajesh (Frontiers in Medicine, 2023)
Several efforts have been made to describe the complexity of T cell heterogeneity during the COVID-19 disease; however, there remain gaps in our understanding in terms of the granularity within. For this attempt, we performed a single-cell transcriptomic analysis of 33 individuals (4 healthy, 16 COVID-19 positive patients, and 13 COVID-19 recovered individuals). We found CD8 + T cell-biased lymphopenia in COVID-19 patients compared to healthy and recovered individuals. We also found an optimal Th1/Th2 ratio, indicating an effective immune response during COVID-19. Expansion of activated CD4 + T and NK T was detected in the COVID-19positive individuals. Surprisingly, we found cellular and metal ion homeostasis pathways enriched in the COVID-19-positive individuals compared to the healthy and recovered in the CD8 + T cell populations (CD8 + TCM and CD8 + TEM) as well as activated CD4 + T cells. In summary, the COVID-19-positive individuals exhibit a dynamic T cell mediated response. This response may have a possible association with the dysregulation of non-canonical pathways, including housekeeping functions in addition to the conventional antiviral immune response mediated by the T cell subpopulation. These findings considerably extend our insights into the heterogeneity of T cell response during and post-SARS-CoV-2 infection.